Pay for performance for specialised care in England: Strengths and weaknesses. Issue 11 (November 2019) - Feng, Yan; Kristensen, Søren Rud; Lorgelly, Paula; Meacock, Rachel; Sanchez, Marina Rodes; Siciliani, Luigi; Sutton, Matt
Highlights: We review and critique a Pay-for-Performance scheme in England for specialised care. We describe contractual arrangements, performance measures, and centralised/decentralised decision making. We discuss strengths and weaknesses based on the international pay-for-performance literature. Abstract: Pay-for-Performance (P4P) schemes have become increasingly common internationally, yet evidence of their effectiveness remains ambiguous. P4P has been widely used in England for over a decade both in primary and secondary care. A prominent P4P programme in secondary care is the Commissioning for Quality and Innovation (CQUIN) framework. The most recent addition to this framework is Prescribed Specialised Services (PSS) CQUIN, introduced into the NHS in England in 2013. This study offers a review and critique of the PSS CQUIN scheme for specialised care. A key feature of PSS CQUIN is that whilst it is centrally developed, performance targets are agreed locally. This means that there is variation across providers in the schemes selected from the national menu, the achievement level needed to earn payment, and the proportion of the overall payment attached to each scheme. Specific schemes vary in terms of what is incentivised – structure, process and/or outcome – and how they are incentivised. Centralised versus decentralised decision making, the nature of the performance measures, the tiered payment structure and the dynamic nature of the schemes have created a sophisticated but complex P4P programme which requires evaluation to understand the effect of such incentives on specialised care.